The efficacy of antihypertensiye drugs in chronic intermittent hypoxia conditions - Diogo, LN (2017)
The authors would like to thank the Portuguese Fundacao para a Ciencia e a Tecnologia (FCT) and CEDOC (Chronic Diseases Research Centre, Lisbon, Portugal). Lucilia N. Diogo is supported by an FCT fellowship (SFRH/BD/48335/2008; PTDC/SAU-TOX/112264/2009).